TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH SEMENTARA (PPATS) AKIBAT KELALAIAN DALAM PEMBUATAN AKTA JUAL BELI TANAH ATAS PERALIHAN HAK ATAS TANAH. - Saputra, Salim; Franciska, Wira; Widyanti, Amelia Nur (SENTRI: Jurnal Riset Ilmiah, 2024)
Negligence in making a sale and purchase deed carried out by the sub-district head as a temporary PPAT will give rise to legal consequences. Thesis research aims to analyze the legal consequences of the Land Sale and Purchase Deed due to the negligence of the Temporary Land Deed Official (PPATS) regarding the transfer of land rights. As well as the responsibility of the Temporary Land Deed Making Officer (PPATS) for negligence in making a land sale and purchase deed for the transfer of land rights. The theory used in this writing uses the theory of legal consequences and the theory of responsibility. The method used is a normative juridical research method by examining library materials or secondary data. How to approach legislation (Statute Approach), Case Approach (Case Approach), and Analytical Approach (Analytical Approach). Sources of legal materials consist of primary, secondary and tertiary legal materials. As well as legal interpretation techniques known in legal science, including Grammatical Interpretation, interpretation based on grammar or linguistics (de gramatikale of taalkundige interpretatie) and Systematic Interpretation, namely research on legal systematics that can be carried out in legislation. From the research results, it was concluded that the legal consequences of the Land Sale and Purchase Deed due to the negligence of the Temporary Land Deed Official (PPATS) regarding the transfer of land rights resulted in the deed being null and void. Such cancellation may cause material and/or immaterial losses to the parties concerned. The responsibility of the Official Making the Temporary Land Deed (PPATS) for negligence in making the Land Sale and Purchase Deed for the transfer of land rights requires individual responsibility and legal responsibility. Legal responsibility takes the form of civil and administrative responsibility. The suggestions from this thesis are that it is hoped that the National Land Agency should further improve its formal and informal guidance to Temporary PPATs. It is best for the Land Deed Making Officer or Temporary Land Deed Making Official to make a land sale and purchase deed to be thorough, careful and careful.